Agro 4.0: Enabling agriculture digital transformation through IoT - Lima, Gustavo; Figueiredo, Fabrício; Barbieri, Armando; Seki, Jorge (Revista Ciência Agronômica, 2021)
A few years have passed since the emergence of the Internet of Things (IoT) technology and its massification. Then, we saw the rise of Industry 4.0 and Agro 4.0, making the digitization of rural areas a hot topic, especially in Brazil where agribusiness is very important for the economy. Nowadays, IoT is already a mature technology, evidenced by cases of successful large-scale implementation of this technology in agricultural production. However, the combination of this technology with others still opens many opportunities, thereby further enhancing the chance to add value to the agricultural production chain. That is, the opportunities within IoT technology are in the aggregation and integration of a set of other disruptive technologies. This article presents a reference review with concepts of IoT, the updated status of this technology, foreseen opportunities, aggregated technologies, the future of IoT, and the vision of practical agricultural implementation in the field in Brazil.